Case study peerelowskiego historyka partyjnego – spostrzeżenia na temat książki Macieja Fica „Rzecznik historii rewolucyjnej”. Henryka Rechowicza (1929–2004) życie publiczne i naukowe - Zaćmiński, Andrzej (Instytut Historii PAN, 2025)
This is a critical analysis of Maciej Fic’s latest book, presenting the biography of Professor Henryk Rechowicz, a historian and political activist from the period of the People’s Republic of Poland. The book should be assessed very highly regarding historical methodology and content. However, it contains some passages of a polemical nature, which provoke questions and comments. They mainly concern the assessment of the attitude and the ‘scientific’ achievements of Rechowicz, a historian in the People’s Republic of Poland, who, as a trusted activist of the Polish United Workers’ Party (PZPR), actively contributed to organising and creating the so-called ‘court science’. At the same time, after 1989, he skilfully found himself in the new political and scientific reality.
p. 257-271
Concerns booki: "Rzecznik historii rewolucyjnej" : Henryka Rechowicza (1929-2004) życie publiczne i naukowe / Maciej Fic. - Katowice : Wydawnictwo Uniwersytetu Śląskiego, 2023.
Summary in English.
Keywords: Rechowicz, Henryk (1929-2004); People’s Republic of Poland; historiography of the People’s Republic of Poland; Polish United Workers’ Party; Poland - 1944-1989 (Polish People's Republic); Poland - 1944-1989 (Polish People's Republic) - historiography